2005
DOI: 10.1200/jco.2005.06.411
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Expression in Pretreatment Biopsies From Head and Neck Squamous Cell Carcinoma As a Predictive Factor for a Benefit From Accelerated Radiation Therapy in a Randomized Controlled Trial

Abstract: This study indicates a key role for the EGFR receptor in determining the proliferative cellular response to fractionated radiotherapy in HNSCC. It also shows that we can select the dose-fractionation regime that has the greatest chance of benefiting the patient. These results also encourage further development of EGFR targeting combined with fractionated radiotherapy in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(141 citation statements)
references
References 30 publications
9
127
1
4
Order By: Relevance
“…Bentzen and co-workers performed IHC on 304 patients randomised to receive CHART vs conventionally fractionated radiotherapy. They concluded that there was a significant benefit from strongly accelerated CHART in patients with high EGFR expression and no benefit in patients with a low EGFR index (Bentzen et al, 2005). These results suggest that the predictive value of EGFR to radiotherapy may be dependent on the dose fractionation regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Bentzen and co-workers performed IHC on 304 patients randomised to receive CHART vs conventionally fractionated radiotherapy. They concluded that there was a significant benefit from strongly accelerated CHART in patients with high EGFR expression and no benefit in patients with a low EGFR index (Bentzen et al, 2005). These results suggest that the predictive value of EGFR to radiotherapy may be dependent on the dose fractionation regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In order to progress to individualized treatment and reduce treatment-related toxicity, patient selection is of major clinical relevance. A well-known method for patient selection is the immunohistochemical detection of EGFR expression in biopsy-derived sections of HNSCC (6,7). However, uncertainties such as biopsy accuracy and tumor heterogeneity affect the specificity and reliability of the procedure, and results showed prognostic value but not predictive value (8).…”
Section: Introductionmentioning
confidence: 99%
“…ERBB1 by hetero-dimerization with other members of the ERBB receptor family (ERBB2, ERBB3, ERBB4), is rapidly activated at a low level in response to therapeutically relevant ionizing radiation exposure (~2 Gy) in multiple tumor cell types, including GBM cells. [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Receptor activation is in part due to the actions of paracrine factors such as heregulins and TGFα, and some laboratories have shown that overexpression of truncated soluble extracellular portions of ERBB1 and ERBB3 can suppress ERBB receptor signaling; thus these molecules could be a useful future yet-to-be-explored gene therapeutic tools in GBM. 86,87 Hence, although irradiation of GBM cells causes death and is used therapeutically, it theoretically also has potential to enhance proliferation in the surviving fraction of cells and promote long-term resistance to multiple cytotoxic stresses.…”
Section: How Are Gbm Cells So Resistant To Therapeutic Intervention? mentioning
confidence: 99%